Hukum Islam di Indonesia Pada Masa Orde Baru (1966-1997) - EMK Alidar (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2012)
During the new order, led by President Soeharto, was a period in which the development of Islamic law seems to stagnate and not grow. It is not independent because of the political policy of the new order government highly extol the sole basis of Pancasila in every aspect of life of the nation. So that the ideologies other than that are to be mitigated as much as possible including religious ideology undertaken to minimize its existence. However, at the end of the period of the reign of the new order regime, there was some very significant changes to the development of Islamic law in Indonesia with the birth of several laws that breathe of Islam.